Biomechanical comparison of conventional versus modified technique in distal chevron osteotomies of the first metatarsal: A cadaver study. Issue 5 (October 2019) - Trost, Matthias; Knieps, Matthias; Loweg, Lennard; Neiss, Wolfram Friedrich; Eysel, Peer; Frey, Sönke; Schulte, Tobias Ludger; Bredow, Jan
Highlights: Distal chevron osteotomy can be performed in a conventional or a modified technique. Using the conventional technique, the average failure strength was 235 N. Using the modified technique, the average failure strength was 210 N. Both techniques showed a comparable biomechanical loading capacity. Abstract: Background: Distal chevron osteotomy can be performed using a conventional or a modified technique. The aim of this biomechanical study was to compare the stability of the two techniques. Methods: Eighteen first metatarsals from nine pairs of fresh frozen human cadaver feet were used. A distal chevron osteotomy was performed using the conventional technique in group 1 (n = 9) and using the modified technique in group 2 (n = 9). The head of the first metatarsals was loaded in two different configurations (cantilever and physiological), using a materials testing machine. Results: In the cantilever configuration, the relative stiffness of the osteosynthesis in comparison with intact bone was 60% (±21%) in group 1 and 65% (±25%) in group 2 ( p = 0.61). In the physiological configuration, it was 47% (±29%) in group 1 and 47% (±21%) in group 2 ( p = 0.98). The failure strength in the cantilever configuration was 235 N (±128 N) in group 1 and 210 N (±107 N) in group 2 ( p = 0.47). Conclusions: The conventional and the modified technique for distal chevron osteotomy in the treatment of hallux valgus show a comparable biomechanical loading capacity in this cadaver study.